Demonstration (web-based) of cryptographic hashing - Lim, Zi Yang (2018)
There is a wide spectrum of topics in the field of computer science. One of which is computer security. Computer security has grown increasingly important due to the rise in cybercrime. To provide a complete education with regards to computer science, Nanyang Technological University (NTU) offers a course, CZ/CE4024 Cryptography and Network Security, for students keen in computer security. It covers the fundamentals of cryptography and network security concepts. An area of the topic covered in the module is Secure Hash Algorithm 3 (SHA-3). The algorithm behind SHA-3 is complex and has multiple steps, each unique and serving different purpose. Due to the complexity, students may find it challenging to fully grasp the theory of SHA-3. This project aims to solve this problem. The approach taken to overcome this issue is to implement a web application which visualises each step of SHA-3. Students do not require additional materials when using the demo, built using AngularJS, to learn about SHA-3. The demo provides step-by-step information on how to derive the final output hash from a plaintext message.